Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2024)
The first paper presents a study that focuses on spatiotemporal historical data organized in an OWL Protégé ontology environment. The application paradigm includes spatial data of local regions and sites of contemporary Greece and Turkey related to Hellenic historical archaeological sites temporally distributed in an extended period from Neolithic Age to the 19th century. The following paper attempts to identify medical and health scientists’ attitude towards the use of hybrid journals, social media and academic networks and the selection factors of publication medium, including alternative metrics. A quantitative survey was conducted, based on a structured questionnaire, focusing on Health Sciences and Medicine, with a population sample mainly consisting of hospital healthcare professionals. Most participants agreed that publishing in hybrid journals results in a significantly high cost for the authors which cannot be paid without funding support and probably affects the validity of the evaluation procedures In the next paper readers will be informed of how the designing of a software tool was done, for computer- assisted learning and translation of Egyptian-Coptic into Greek. The software design emphasizes the ability of processing inscriptions on artifacts through a simple interactive interface for its usage by Greek-speaking scholars of Humanities, having just essential familiarization with computers. The last paper contributes to the study of cultural heritage by exploring the possibility of delving deeper into a number of its fields through a single monument. For this purpose, authors applied contemporary informal education approaches to the design of an educational program for cultural monuments taking Hadrian’s aqueduct as the starting point. The rich interdisciplinary approach that emerged from the study of a single monument, its capacity to “narrate” stories as well as the potential of its gainful employment by young people, aiming at their cultural awareness concerning world cultural heritage of monuments.